Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4028/www.scientific.net/amm.508.208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Axial Load on the Seismic Behavior of RC Beam-Column Joints with Wide Beam

Abstract: Beam-column joints can play a key role on the seismic behavior of reinforced concrete buildings. Until now studies and experimental investigations on this topic have been mainly focused on beam-column joints with stiff beams, i.e. beams with height larger than the thickness of the adjacent floor slab. However, especially in the European residential building stock, frame structures are often equipped with wide - therefore rather flexible - beams. However, not many studies have been devoted so far to this type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…As previous experimental studies demonstrated [25,26], the fragile failure mechanism of code conforming wide beam-column joints where damage and slip phenomena occurring to the beam rebars bonded out of the column core cause sudden strength decay and, as a consequence, a low displacement ductility ratio. Before setting up a new expensive experimental program to assess the feasibility of such an FRP-based strengthening intervention, a detailed numerical model by using the finite element software package ATENA 3D [27] has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…As previous experimental studies demonstrated [25,26], the fragile failure mechanism of code conforming wide beam-column joints where damage and slip phenomena occurring to the beam rebars bonded out of the column core cause sudden strength decay and, as a consequence, a low displacement ductility ratio. Before setting up a new expensive experimental program to assess the feasibility of such an FRP-based strengthening intervention, a detailed numerical model by using the finite element software package ATENA 3D [27] has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the influence of temperature on the failure modality of stub CFST structural members could be referred to in Yan et al [99] (low temperature) and Lyu et al [97] (high temperature). Finally, Angelo et al [100] and Kulkarni et al [101] have tested and discussed about the failure of rectangular CFST structural members in junction with wide beam for earthquake engineering application. It is worth mentioning that only rectangular CFST columns (i.e., depth/width ratio greater than 1) were collected for investigation.…”
Section: Data Used and Selection Of Variablesmentioning
confidence: 99%
“…The maximum axial load considered and well documented in the form of shear strength equation is 0.42 f ′ c A g as in the case of Sarsam and Phillips (1985). Masi et al (2014) conducted experimental work on full-scale beam-column joints with wide beam to study the effect of axial load on the behavior of BCJ; the values of axial load ratio considered were 0.15 and 0.3. The results showed that the deformation and ductility are affected by the magnitude of column axial load.…”
Section: Introductionmentioning
confidence: 99%